2020
DOI: 10.1055/s-0040-1714344
|View full text |Cite
|
Sign up to set email alerts
|

Vaginal Birth after Two Previous Cesarean Sections versus Elective Repeated Cesarean: A Retrospective Study

Abstract: Objective Trial of labor after cesarean delivery (TOLAC) is a common practice worldwide but the evidence is still scant regarding this practice in women who underwent 2 previous cesareans. The purpose of this study is to retrospectively review our experience with vaginal birth after two previous cesarean sections (VBA2C), with specific attention to the indications for previous cesarean and to the women's motivation for attempting trial of labor. Study Design This was a retrospective cohort study co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 25 publications
2
4
1
Order By: Relevance
“…However, these studies were limited by small sample sizes and were retrospective in nature. The present study is the first large, prospective cohort study to examine TOLA2C in a low‐resource setting and supports professional society recommendations for TOLA2C when individualized counseling is provided and key criteria are met 3,16 …”
Section: Discussionsupporting
confidence: 70%
See 3 more Smart Citations
“…However, these studies were limited by small sample sizes and were retrospective in nature. The present study is the first large, prospective cohort study to examine TOLA2C in a low‐resource setting and supports professional society recommendations for TOLA2C when individualized counseling is provided and key criteria are met 3,16 …”
Section: Discussionsupporting
confidence: 70%
“…This success rate is within the range of the known threshold of 65%–85% in women who have had one or two previous CSs 4,5,18 . Previous studies 7,18 in medium‐ and high‐resource countries have also shown encouraging rates: 62.8% in Poland, 18 71% and 76.1% in Italy, 3,7 and 88% in Israel 19 . However, these studies were limited by small sample sizes and were retrospective in nature.…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…A prior cesarean section is the most common indication of ERCS (Kietpeerakool et al, 2019). The success rate of VBAC ranges from 60% to 80 %( De Leo et al, 2020). In unsuccessful cases, serious complications such as uterine rupture are associated with morbidity (Levin et al, 2020).…”
Section: Introductionmentioning
confidence: 99%